2015
DOI: 10.1002/cncr.29489
|View full text |Cite
|
Sign up to set email alerts
|

Quality of patient‐reported outcome reporting across cancer randomized controlled trials according to the CONSORT patient‐reported outcome extension: A pooled analysis of 557 trials

Abstract: Background The main objectives of this study were to identify the number of randomized controlled trials (RCTs) that have included a patient-reported outcome (PRO) endpoint across a wide range of cancer specialties and to evaluate completeness of PRO reporting according to the CONSORT PRO extension. Methods RCTs with a PRO endpoint, conducted across several cancer specialties and published between 2004 and 2013 were considered. Studies were evaluated based on previously defined criteria, including the CONSOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
81
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 31 publications
12
81
0
2
Order By: Relevance
“…Diversity in applied PRO methodologies and poor quality of PRO reporting from clinical trials has previously been reported (Brundage et al , 2011a; Lemieux et al , ; Dirven et al , ; Efficace et al , , ; Bylicki et al , ; Hamel et al , ). However, to our knowledge, this is the first review to investigate methodological aspects in PRO measurements and analyses in studies of patients with MM.…”
Section: Discussionmentioning
confidence: 96%
“…Diversity in applied PRO methodologies and poor quality of PRO reporting from clinical trials has previously been reported (Brundage et al , 2011a; Lemieux et al , ; Dirven et al , ; Efficace et al , , ; Bylicki et al , ; Hamel et al , ). However, to our knowledge, this is the first review to investigate methodological aspects in PRO measurements and analyses in studies of patients with MM.…”
Section: Discussionmentioning
confidence: 96%
“…Again, these are knowledge transfer concerns requiring intervention to improve reporting practices and to ensure PRO results are interpreted accurately so they can appropriately inform patient care. Recent reviews confirm that reporting of PRO endpoints remains unsatisfactory overall; particularly regarding the reporting of PRO hypotheses, methodology, missing data, and generalisability of results [19][20][21][22][23][24][25][26]. Failing to report this information is wasteful as it limits the potential for readers to appraise the effect of interventions on patient health status, and the potential for PRO systematic reviews to impact clinical recommendations and health policy [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…It may also decrease clinicians' confidence in the value of PRO data [29]. These aforementioned reviews [19][20][21][22][23][24] predominately include RCTs published before CONSORT-PRO. We expect that adherence to CONSORT-PRO will improve with time, as awareness and uptake increases.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of health‐related quality of life (HRQoL) outcomes in medical research is now critical to better inform patient care and to facilitate clinical decision‐making. Cancer clinical trials, for example, now frequently include HRQoL as an outcome (either primary or secondary) along with more traditional clinical or laboratory outcomes . In studies including a HRQoL evaluation, an important aspect is often the estimate of the average treatment effect on the treated (ATT) on patients' self‐reported health status and/or symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer clinical trials, for example, now frequently include HRQoL as an outcome (either primary or secondary) along with more traditional clinical or laboratory outcomes. 1 In studies including a HRQoL evaluation, an important aspect is often the estimate of the average treatment effect on the treated (ATT) on patients' self-reported health status and/or symptoms. ATT is the expected difference between observed outcomes of treated subjects and those they would experience had they not been treated (unobserved).…”
Section: Introductionmentioning
confidence: 99%